Technical note: Investigating the suitability of existing facilities for a new Lu‐177 prostate‐specific membrane antigen therapy program. Issue 4 (16th January 2023) - Murtha, N.; Morrison, H.; Roumeliotis, M.; Quirk, S.; Smith, W.; Blais, A.
Abstract: Background: 177 Lu prostate‐specific membrane antigen (PSMA) therapy prolongs survival for some prostate cancer patients. To adopt this technique, institutions may need to evaluate the suitability of existing infrastructure. Purpose: Develop a methodology to determine whether existing facilities can accommodate a 177 Lu‐PSMA therapy program. Methods: Room suitability is defined by both the ability to accommodate 177 Lu‐PSMA therapy workflow and to provide appropriate radiation shielding. Two methods of shielding calculation were performed: (1) National Council on Radiation Protection and Measurements report 151 (NCRP‐151), with workload defined in terms of the activity of 177 Lu administered, and (2) using the RadPro shielding calculator. This methodology was applied to 131 I therapy, PET‐CT uptake, PET‐SPECT injection, and orthovoltage therapy rooms. Results: 131 I therapy rooms were found to meet both shielding and workflow requirements. The shielding was found to be adequate for orthovoltage and PET‐SPECT facilities, neglecting patient transit between external washrooms. The workflow was the limiting factor for these rooms due to the requirement of dedicated washrooms that shield the patient and contain possible contamination. The PET‐CT facility did not meet either criteria. The NCRP‐151 method generally predicted a higher dose rate on the other side of shielding than did the RadPro calculator. The dose rate on the other side of concrete shielding as predicted by the NCRP‐151 method increased relative to the dose rate predicted by the RadPro calculator as shielding thickness increased. For lead shielding, the dose rate predicted by the NCRP‐151 method decreased relative to the result predicted by the RadPro calculator with increasing material thickness. Conclusions: 131 I therapy, PET‐CT uptake, PET‐SPECT injection, and orthovoltage therapy rooms were considered. The 131 I treatment rooms were the best candidate for 177 Lu‐PSMA therapy, due to their shielding and capability to accommodate the necessary workflow.